The prefixes bio and eco and their relation to Forestry Sciences - Arce, Rodrigo (2025)
This article addresses the relationship between words containing the prefixes bio and eco and For- est Sciences. The article´s objective is to support the strategic importance for Forestry expanding is knowledge and practices by incorporating the conceptual development of the words contain- ing the prefixes bio and eco into its philosophical, theoretical, methodological, and procedural frameworks. From this review and reflection, it is clear that the it is clear that the language of forest, framed within Cartesian epistemology and a disjunctive ontology, is restricted to conven- tional view of its object of study, which refers to forests in terms of management, conservation, and restoration. This institutionalized, normalized, and standardized language is reinforced by national and international institutions that reflect economic and political interests. However, by understood as socio-ecosystems that are part of a complex reality, the scope of action expands to global level, emphazing interdependent relationships and focusing on the preservation of life in all its manifestations. Knowledge and application of terms that include the prefixes bio and eco are relevant to forestry sciences, as they provide tools for describing, interpreting, and explaining the relationships between humans and forests.